Synthesis of some fused heterocycles from laboratory available starting materials - Mohamed Sayed Mohamed Mohamed Farghaly; Fathy Mohamed Abdelrazek; Sobhy Mohamed Gomaa (Cairo : Mohamed Sayed Mohamed Mohamed Farghaly, 2020)
A novel series of 1,5-dihydropyrido-triazolo-pyrimidine derivatives were prepared by cyclocondensation of 2-thioxo-pyrido[2,3-d]pyrimidines (prepared from reaction of chalcone with 6-aminothiouracil) with a variety of hydrazonoyl chlorides. 3-Methyl-5-oxo-4-(2-arylhydrazono)-4,5-dihydro-1H-pyrazole-1-carbothioamides (obtained from the reaction of ethyl 3-oxo-2-(2-arylhydrazono)butanoates with thiosemicarbazide) could be transformed into a variety of thiazolyl-pyrazole derivatives via their reaction with a diversity hydrazonoyl chlorides as well as bromoacetyl derivatives. Grinding a mixture of 6-aminopyrimidine-2,4-(1H, 3H)dione, 6-amino-2-thioxo-2,3- dihydropyrimidine-4(1H)-one or ethyl 7-amino-5-oxo-1-aryl-1,5-dihydro[1,2,4]-triazolo[4,3- a]pyrimidine-3-carboxylate derivatives with 1,2-diphenylethanone and different aromatic aldehydes in presence of aluminate sulfonic acid nanoparticles (ASA NPs) in a one pot solvent-free conditions, afforded the pyrido[2,3-d]pyrimidinone derivatives and ethyl 5-oxo- 1-aryl-6,7,8-triphenyl-1,5,6,9-tetrahydropyrido[2,3-d][1,2,4]triazolo[4,3-a]pyrimidine-3- carboxylate derivatives respectively. All structures were elucidated by spectral and elemental analyses. Some structures were further proved by alternative synthesis. Some of the synthesized compounds are forced for molecular docking by using MOE 2014.010 Package software; one of in-silico study tools. These compounds are targeting Human Cyclin Defendant Kinase 2 (CK2) PDB ID (1PXO.Protein data bank) due to its important role in controlling of the human cell cycle and also for meiosis. Moreover, the computational studies were carried out for some new compounds.The results indicated that these compounds showed promising binding affinities against the active site of the epidermal growth factor receptor kinase (EGFR)
Thesis (Ph.D.) - Cairo University - Faculty of Science - Department of Organic Chemistry
Issued also as CD
Keywords: Cyclocondensation; Hydrazonoyl halides; Pyrido[2,3-d]pyrimidine